IMPLEMENTASI ALGORITMA ADVANCED ENCRYPTION STANDARD (AES) UNTUK MENINGKATKAN KEAMANAN PASSWORD PADA APLIKASI TO-DO LIST BERBASIS ANDROID DENGAN METODE AGILE - Dede Sahrul Bahri; Muhammad 'Arda Rizqy Fauzan (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
Applications that implement user authentication, such as the To-Do List Application, often store sensitive information, requiring strong security protection. Passwords serve as the primary key for user authentication and must be secured to prevent unauthorized access. Therefore, this study applies the Advanced Encryption Standard (AES) algorithm to the To-Do List Application to enhance password security. AES was chosen due to its high level of security and efficiency, making it highly effective in safeguarding user data. The Agile method was utilized to ensure flexibility and responsiveness to requirements throughout the application development process. This approach allows for a more efficient development process while maintaining quality. The result of this research is an Android-based To-Do List Application that not only meets user needs but also provides a high level of security, ensuring users feel more comfortable using the application.